Classification of heart sound based on S-Transform and neural network - H. M., Hadi; Mohd Yusoff, Mashor, Prof. Madya Dr.; Mohd Zubir, Suboh; Mohamed Sapawi, Mohamed (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/